Inaugural ASEAN-China Maritime Exercise : What To Expect - Koh, Colin Swee Lean (2018)
While largely symbolic, the inaugural ASEAN-China Maritime Exercise serves as a first step forward in promoting practical measures for confidence-building and maritime safety despite ongoing disputes in the South China Sea.